1999
DOI: 10.1094/pdis.1999.83.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Sensitivities of Venturia inaequalis Populations to the Strobilurin Fungicide Kresoxim-methyl

Abstract: The efficacies of the new strobilurin fungicide kresoxim-methyl for the protection of apple leaves from infection by baseline populations of Venturia inaequalis were uniform across five major apple growing regions in North America. The mean ED50 value determined for 25 populations was 0.35 μg ml-1, with values ranging from 0.11 μg ml-1 to 0.75 μg ml-1. The mean level of scab control achieved at the kresoxim-methyl dose of 4 μg ml-1 was 93%. For one of the five orchards sampled in each region, kresoxim-methyl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
2
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 23 publications
6
44
2
2
Order By: Relevance
“…Venturia inaequalis sensitivity to mancozeb was determined according to a previously described procedure (Köller et al, 1999) in brief conidial suspensions in SDW obtained from 4 to 6 wk old monoconidial cultures where 30 to 50 µL were spread on aPDA amended with the tested fungicide in concentrations ranging from 0 to 10 µg mL -1 and incubated for 24 h. Germination of 100 conidia was assessed in four replicate plates for each fungicide concentration. A conidium was considered germinated when its germinating tube was at least 1.5 times its own length.…”
Section: Sensitivity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Venturia inaequalis sensitivity to mancozeb was determined according to a previously described procedure (Köller et al, 1999) in brief conidial suspensions in SDW obtained from 4 to 6 wk old monoconidial cultures where 30 to 50 µL were spread on aPDA amended with the tested fungicide in concentrations ranging from 0 to 10 µg mL -1 and incubated for 24 h. Germination of 100 conidia was assessed in four replicate plates for each fungicide concentration. A conidium was considered germinated when its germinating tube was at least 1.5 times its own length.…”
Section: Sensitivity Assaysmentioning
confidence: 99%
“…Fungicide resistance in V. inaequalis is well documented worldwide for old fungicides such as dodine (Köller et al, 1999;Broniarek-Niemiec and Bielenin, 2008), benzimidazole (Koenraadt et al, 1992), demethylation inhibitors (DMIs) (Sholberg and Haag, 1993;Köller et al, 1997), and newer fungicides such as strobilurins (Olaya and Koller, 1999;Fontaine et al, 2009) and anilinopyrimidines (Küng et al, 1999). There are no reports in the literature about sensitivity to mancozeb, an old fungicide still used for apple scab control, used alone or mixed mainly with DMIs as an anti-resistance strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and molecular studies have shown that resistance to QoI fungicides could appear either by a target site modification through point mutations in the Qo site of cytochrome b (Di Rago and Colson, 1989;Zheng and Ko¨ller, 1997;Zheng et al, 2000) or by increased electron transfer through the alternative oxidase pathway (Ziogas et al, 1997;Olaya and Ko¨ller, 1999a;Tamura et al, 1999). However, alternative respiration appears to play no significant role in pathogenesis on QoI-treated plants in natural populations of pathogens controlled by these fungicides (Ziogas et al, 1997;Olaya and Ko¨ller, 1999b) possibly because host flavones released during infection interfere with induction of this pathway (Zheng et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Second, plant antioxidants, such as flavones, are released during infection and interfere with the induction of alternative respiration by quenching reactive oxygen species that are necessary to induce the AOX gene and are generated by QoIs (Wood & Hollomon, 2003). Despite the widely accepted minor role of AOX in QoI resistance, several reports using alternative oxidase-deficient mutants and specific inhibitors of this enzyme have revealed that alternative respiration also limits QoI effectiveness in planta, especially once the infection has been established (Olaya & Köller, 1999;Avila-Adame & Köller, 2003;Miguez et al, 2004). A possible explanation is that a decreasing demand for energy efficiency during the later stages of the infection process, such as mycelial growth and sporulation, enables AOX to become more effective as an infection progresses (Wood & Hollomon, 2003).…”
Section: Alternative Respirationmentioning
confidence: 99%